Analysing the Portuguese Urban System from a Quality of Life Viewpoint - Paula Costa; José Mendes; Rui Ramos (European Regional Science Association (ERSA), 2001)
The Portuguese urban system is unbalanced, mainly due to the presence of two major cities and absence of medium sized cities. In fact, the biggest city (Lisbon) has around 570 thousand inhabitants, the second biggest city (Porto) has around 275 thousand inhabitants and the third one has only 120 thousand inhabitants. From the point of view of Quality of Life, there is a perception that the unbalance is even greater. This paper stands on a study on Quality of Life (QoL) in the major eighteen cities in Portugal, developed during 1999 and 2000. A global QoL index and nine QoL dimensional indexes were calculated and weighted by the population living in the cities. The QoL dimensions considered in the study were: Climate; Commerce and Services; Crime; Unemployment; Housing; Mobility; Architectural Patrimony; Purchasing Power; and Pollution. To evaluate each dimension some indicators have been created, taking into account the relevance of the variables and the availability of data. The study produced city scores and rankings. The results of the study were integrated in a GIS-based database and were used to “redesign” the Portuguese urban system, from the QoL point of view. For this, QoL index and population database were crossed in order to evaluate the levels of inhabitants submitted to different levels of Quality of Life. QoL deficits were identified, spatial-referenced, and discussed. Note: Unfortunately only today I have the confirmation of being able to write the final communication before June 30th, 2001. So I send this abstract even after the closing date for submission of abstracts. Hoping to have good news from you soon. Yours sincerely, Rui Ramos
Keywords: 330